The Relationship between Endothelial Dysfunction and Endothelial Cell Markers in Peripheral Arterial Disease - Igari, Kimihiro (PLoS One, 2016)
INTRODUCTION: The endothelial function plays key roles in both promoting and protecting against atherosclerotic disease. Several methods, including peripheral arterial tonometry (PAT), have been reported to be useful for investigating endothelial dysfunction. Furthermore, the level of thrombomodulin (TM) is assumed to reflect the endothelial dysfunction. In the present study, we investigated endothelial dysfunction in patients with peripheral arterial disease (PAD) by measuring their TM levels, and evaluated the correlation between TM and various parameters. MATERIALS AND METHODS: We measured the TM levels and performed PAT in 17 patients with PAD. We also recorded the patients’ demographic information, including comorbidities, and investigated their hemodynamic status by measuring the ankle brachial pressure index (ABI). The PAT results were used to calculate the reactive hyperemia index (RHI), which reflected the patients’ level of endothelial dysfunction. RESULTS: The RHI and ABI values and the serum level of creatinine were found to be significantly correlated with the TM level (P = 0.040, 0.041 and 0.005, respectively). After setting an RHI value of 1.67 as the cut-off, the patients with RHI values of <1.67 were found to have significantly higher TM levels (median, 20.3 U/mL) than the patients with RHI values of ≥1.67 (median, 13.7 U/mL) (P = 0.023). CONCLUSIONS: The degree of endothelial dysfunction, as calculated by the TM level, might influence the prognostic value of the RHI, which is determined by PAT. The measurement of the TM level and PAT might both be useful methods of measuring endothelial dysfunction in patients with PAD.